2006
DOI: 10.1080/09273940600678062
|View full text |Cite
|
Sign up to set email alerts
|

Visual Recovery FollowingMycobacterium chelonaeEndophthalmitis

Abstract: Following uncomplicated cataract surgery, a patient receiving etanercept for psoriatic arthritis developed Mycobacterium chelonae endophthalmitis. Vitrectomy, capsulectomy, and intraocular lens removal was followed by intravitreal amikacin, topical gatifloxacin, intravenous imipenem, and oral clarithromycin for six months. The patient achieved a final corrected visual acuity of 20/20. Etanercept has been implicated in the development of numerous, severe granulomatous infections, though not previously with M. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Etanercept therapy has been reported in association with fatal MACLD [160], fatal pulmonary M. xenopi infection [161], fatal pulmonary M. abscessus infection [162], M. chelonae endophthalmitis [163], M. xenopi spinal osteomyelitis [164] and pulmonary M. szulgai infection [165]. In the latter case, the patient's treatment changed from etanercept to adalimumab after M. szulgai was identified.…”
Section: Tnf-a Antagonistsmentioning
confidence: 99%
“…Etanercept therapy has been reported in association with fatal MACLD [160], fatal pulmonary M. xenopi infection [161], fatal pulmonary M. abscessus infection [162], M. chelonae endophthalmitis [163], M. xenopi spinal osteomyelitis [164] and pulmonary M. szulgai infection [165]. In the latter case, the patient's treatment changed from etanercept to adalimumab after M. szulgai was identified.…”
Section: Tnf-a Antagonistsmentioning
confidence: 99%
“…From literature review, there were only 11 eyes that showed nal BCVA of 6/60 or better [7,21,30,32,37,41,43,47,52]. Stewart et al reported a case of M. abscessus endophthalmitis with a full visual recovery [50].…”
Section: Discussionmentioning
confidence: 99%
“…Causes of M. chelonae endophthalmitis include prior cataract surgery,912 glaucoma surgery,13 iridocyclitis,14 intravitreal steroid injections,9,15 neurotrophic cornea,9 and systemic immunosuppression 16,17. The patient had several risk factors for an ocular RGNTM infection: 1) an immunosuppressed state after completion of chemotherapy during which herpes zoster infections are more common; 2) a neurotrophic cornea secondary to HZO with a non-healing ulcer and recurrent perforations; and 3) multiple diagnostic and therapeutic ocular surgeries, long-term antibiotic therapy, and steroid immunosuppression during periods of active infection.…”
Section: Discussionmentioning
confidence: 99%